Implikasi Pemahaman Birrul Walidain pada Materi Pendidikan Agama Islam dalam Membentuk Sikap Sosial dan Etika Siswa Kelas X SMA Takhasus Al-Qur’an Wonosobo - Bambang Sugiyanto; Robingun Suyud El-Syam; Ina Niatul Maidah (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
Islamic Religious Education plays a strategic role in instilling moral values, particularly birrul walidain, as a foundation for shaping students’ social attitudes and ethics. This study aims to examine the implications of students’ understanding of birrul walidain in Islamic Religious Education learning on the social attitudes and ethics of tenth-grade students at SMA Takhassus Al-Qur’an Wonosobo. This research employed a qualitative approach with a field research design. The research subjects consisted of Islamic Religious Education teachers, tenth-grade students, and parents. Data were collected through observation, interviews, and documentation. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The findings indicate that students’ understanding of birrul walidain is conceptually adequate but remains largely cognitive and has not been consistently internalized into daily behavior. This understanding significantly influences students’ social attitudes and ethics, as students with better understanding tend to demonstrate respect, empathy, and social responsibility. Therefore, Islamic Religious Education learning should be optimized through role modeling, habituation, and contextual learning to ensure that the value of birrul walidain is reflected in students’ actual behavior.